(No^ERKI PO ISTORII GARMONII W RUSSKOJ MUZYKE(B.s (NWYPUSK (BIIIs ((NmOSKWAs (NmUZYKAs, 1989)
(NtRETIJ WYPUSK WKL@^AET O^ERKI PO ISTORII GARMONII p(B.(Ni(B.(N~AJKOWSKOGO s(B.(Nw(B.(NrAHMANINOWA I a(B.(Nn(B.(NsKRQBINA(B.s
Keywords: (NtEORIQ(B.s